Analisis Pengaruh Corporate Governance, Corporate Social Responsibility, dan Corporate Financial Performance terhadap Perusahaan Indeks Kompas100 (The Influence Analysis of Corporate Governance, Corporate Social Responsibility, and Corporate Financial Performance to Companies in Kompas100 Index) - Annisa Putri Caesari; Abdul Kohar Irwanto; Muhammad Syamsun (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2015)
The main objective of a company in running its operational activities is to maximize profit. Apart from that, the company is also obliged to provide maximum contribution to the community. To accommodate the objectives and obligations, the company may apply a system called Corporate Governance (CG). The company can also implement Corporate Social Responsibility (CSR) as its significant step in contributing to the community. The implementation of CG and CSR is related because CSR is a consequence of CG implementation. In addition to CG and CSR are interconnected, CG and CSR are also interconnected with Corporate Financial Performance (CFP). Through the implementation of CG, the company can improve CFP. The relationship between CSR and CFP can be associated positively or negatively. The research was conducted on 100 companies listed in Kompas100 index to determine the influence of CG to CSR, influence of CG to CFP, influence CSR to CFP, and influence of CG to the CFP with CSR as a moderating variable. Structural equation modeling (SEM) analysis was used to determine the relationship of these three variables. The results showed that CG influenced positively to CSR, but influenced negatively to CFP. Likewise, CSR influenced negatively to CFP. Due to the negative influence of CG to CFP and CSR to CFP, CG also influenced negatively to the CFP through the disclosure of CSR as moderating variable.Keyword: corporate governance, corporate social responsibility, corporate financial performance, Indeks Kompas100